The future of securitization - Günter Franke; Jan Pieter Krahnen (Goethe University Frankfurt, Center for Financial Studies (CFS), 2008)
Securitization is a financial innovation that experiences a boom-bust cycle, as many other innovations before. This paper analyzes possible reasons for the breakdown of primary and secondary securitization markets, and argues that misaligned incentives along the value chain are the primary cause of the problems. The illiquidity of asset and interbank markets, in this view, is a market failure derived from ill-designed mechanisms of coordinating financial intermediaries and investors. Thus, illiquidity is closely related to the design of the financial chains. Our policy conclusions emphasize crisis prevention rather than crisis management, and the objective is to restore a 'comprehensive incentive alignment'. The toe-hold for strengthening regulation is surprisingly small. First, we emphasize the importance of equity piece retention for the long-term quality of the underlying asset pool. As a consequence, equity piece allocation needs to be publicly known, alleviating market pricing. Second, on a micro level, accountability of managers can be improved by compensation packages aiming at long term incentives, and penalizing policies with destabilizing effects on financial markets. Third, on a macro level, increased transparency relating to effective risk transfer, risk-related management compensation, and credible measurement of rating performance stabilizes the valuation of financial assets and, hence, improves the solvency of financial intermediaries. Fourth, financial intermediaries, whose risk is opaque, may be subjected to higher capital requirements.
urn:nbn:de:hebis:30-58871
Keywords: D82; G14; G21; G28; G30; 330; Financial Crisis 2007/08; Bank Regulation; First Loss Position; Rating Process; Securitization; Transparency; Securitization; Marktliquidität; Finanzmarktkrise; Bankenaufsicht; Finanzintermediär; Ökonomischer Anreiz; Bankenaufsicht; Welt